Self-Perception of Identity Unity Amid Diversity in A Murui/Uitoto Myth - Escobar, Flor Angela Buitrago; Collazos, Girley; Bohorquez, Mabel (Journal of Posthumanism, 2025)
The main objective of this article is to present the relationship among identity, language and genetics from a premise that considers the point of view of the participating group. The Murui/Uitoto indigenous people (in the Colombian Amazon) have had a self-perception of identity diversity, despite different linguistic groups and dialectal variations. In our western view, we need DNA testing to explain genetic bonding among indigenous populations, but they already have a self-perception of that unity amid diversity: this reality is reflected in a myth. The article will first present the myth and the background to understand the linguistic convergence areas; then, the context of the research with the Murui people in Caquetá (Colombia). The conclusions will explain the reasons for using this kind of presentation and will summarize how the aspects underpin identity self-perception.